SH?DAN SHUGI DALAM MANGA SHINSENGUMI IMON PEACE MAKER KARYA NANAE CHRONO - Suadnyana, I Made Ady (Humanis; Volume 5. No. 3. Desember 2013)
The analysis showed that the values of sh?dan shugi that contained in Shinsengumi group are ba and shikaku, shuj? kankei, ittaikan and ky?d?tai, relationships between senpai and k?hai, amae, as well as on and giri. The value Ba and shikaku in Shinsengumi group is characterized by a sense of sacrifice for the sake of the group. Shuj? kankei is relationship between superiors and subordinates that well established. Nakama sh?dan included by ky?d?tai and ittaikan which capable to creat the solidarity. Nakama relation between senpai and k?hai goes well. There are also amae that can make a sense of comfort among the group members and giri as embodiment of reciprocation from group members who had received on.
Keywords: Sh?dan Shugi, Shinsengumi, Manga